(untitled) (Medical Forum Monthly, 2024)
Objective: To examine the gender differences in clinical presentation of acute coronary syndrome in patients presenting to tertiary care hospital. Study Design: Retrospective cohort study Place & Duration of Study: This study was conducted at the Department of Cardiology, Bolan Medical Complex Hospital Quetta from January 2019 to June 2019. Materials and Methods: One hundred and fifty patients of both genders with ages 20 to 80 years presented with acute coronary syndrome were enrolled in this study. Patients were divided according to gender. Clinical presentation, risk factors and severity of coronary artery disease were examined. Results: There were 114 (76%) patients were males and 24% patients were females. Female patients were older than male 60.2±8.7 vs 58.8±9.5 years. STEMI was found in 68 (45.33%) patients, non-STEMI was found in 36 (24%) patients and unstable angina was found in 46 (30.67%) patients. In comparison of risk factors between male and females, we found male patients were significantly higher as compared to females (p=<0.05). Conclusion: Female patients were older than males. Smoking, family history of CAD, hypertension were common risk factors and male patients were higher than females regarding risk factors.